Memaknai Intergritas Sektor Publik Dalam Tata Kelola Pemerintahan Kelurahan Yang Lebih Baik - Purwanti, Tri; Gunawan , Gunawan; Fadilah, Annisa Raikhan; Nurhasanah, Essa; Rahmawati, Rahmawati (Universitas Dehasen Bengkulu, 2023)
Good governance at the kelurahan level is an important aspect in maintaining the sustainability and welfare of local communities. One of the key elements in better urban village governance is public sector integrity. Public sector integrity includes aspects of honesty, transparency, accountability, and professionalism in carrying out their duties and responsibilities. The importance of interpreting public sector integrity in better urban village governance lies in efforts to reduce corruption, nepotism, and collusion that often hinder equitable and quality development and public services. Integrity is the main foundation in creating a clean and efficient government environment. In the context of urban governance, public sector integrity relates not only to the individual behavior of government officials, but also includes systems and procedures that support transparency and accountability in the management of public resources. This involves rigorous oversight from various parties, including local communities and independent oversight institutions. Enforcing public sector integrity in kelurahan governance requires the adoption of clear policies and consistent implementation. It also requires coaching and training for government officials to have a deep understanding of the importance of integrity in carrying out their duties.